2008
DOI: 10.1007/s00127-008-0489-8
|View full text |Cite
|
Sign up to set email alerts
|

The strengths and difficulties questionnaire: validation study in French school-aged children and cross-cultural comparisons

Abstract: The study provided good support for the validity of the parent-reported SDQ in France as well as evidence for the usefulness of the SDQ as a promising screening instrument for epidemiological research and clinical purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
84
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 29 publications
12
84
1
6
Order By: Relevance
“…This is natural because generally, every country has the different cut-off, even in Sweden and Norway it is found that the cut-off ≥ 4 (Malmberg et al, 2003;Ullebo et al, 2011). It depends on the gold standard used and the culture that exists in each country (Becker et al, 2006;Shojaei et al, 2009). …”
Section: The Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is natural because generally, every country has the different cut-off, even in Sweden and Norway it is found that the cut-off ≥ 4 (Malmberg et al, 2003;Ullebo et al, 2011). It depends on the gold standard used and the culture that exists in each country (Becker et al, 2006;Shojaei et al, 2009). …”
Section: The Discussionmentioning
confidence: 99%
“…Japan's SDQ-PR has good reliability for all its subscales (α = 0.52-0.77) and the cut-off of the SDQ-PR hyperactivity subscale is the same as the English SDQ-PR (Matsuishi et al, 2008). The French SDQ-PR has good internal consistency (α = 0.54-0.74) and the same cut-off as the English and American SDQ-PR on almost all subscales, except the prosocial subscale where the cut-off is lower than English and American (Shojaei, Wazana, Pitrou & Kovess, 2009). The Chinese SDQ has an internal consistency with α = 0.45-0.81 for SDQ-PR and α = 0.55-0.84 for SDQ-TR.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…La mère doit répondre aux questions à l'aide d'une échelle de type Likert à 3 points allant de 0 (Pas vrai) à 2 (Très vrai) en se référant aux comportements de son enfant au cours des six mois précédents. Lors de la validation de la version française du SDQ, les auteurs ont trouvé des indices de cohérence interne allant de α = .46 à α = .74 (Shojaei, Wazana, Pitrou et Kovess, 2009). Une étude visant à comparer les scores obtenus au SDQ et au Child Behavior Checklist (CBCL) (Achenbach, 1991) met en relief des corrélations très élevées entre les deux mesures qui permettent de distinguer les enfants d'un échantillon à risque élevé d'un point de vue psychiatrique de ceux d'un échantillon à faible risque (R. Goodman et Scott, 1999).…”
Section: Instruments De Mesureunclassified
“…Secondly, these normative data come from the US and should be used with caution in a French-speaking European culture. This latter point is particularly challenging considering that some cultural differences have been found in other psychopathology screening measures between French-speaking countries (e.g., France) and the US (e.g., see Shojaei, Wazana, Pitrou, & Kovess, 2009), and between the Flemish community of Belgium and the US (Braet et al, 2011).…”
Section: Introductionmentioning
confidence: 99%